Simulated fluid resuscitation for toddlers and young children: effect of syringe size and hand fatigue. Issue 3 (9th December 2014) - Toshniwal, Gokul; Ahmed, Zulfiqar; Sengstock, David; Anderson, Brian
Summary Background In small children, fluid resuscitation requires rapid administration of a relatively large fluid volume. This is often achieved manually. The optimal syringe size is unknown. Objectives The purpose of this study was to determine which syringe delivers fluid in the shortest time. The secondary outcome was to determine which syringe was associated with hand fatigue. Methods Participants (n = 20) performed a simulated fluid resuscitation using four syringe sizes: 5 ml, 10 ml, 20 ml, and 60 ml. The 'pull and push' method was used to transfer 250 ml of lactated Ringer's solution from a bag, through IV tubing, into a container. Fluid transfer time (seconds) and hand fatigue were measured. Results A 'U'‐shaped curve was identified between syringe size and transfer time (P < 0.0001). The 10‐ml and 20‐ml syringes did not differ significantly (231 ± 43 vs 228 ± 45 s, P > 0.2, respectively). The 5‐ml and 60‐ml syringes did not differ significantly (273 ± 69 s vs 295 ± 64, P = 0.2, respectively). However, the 5‐ml syringe required significantly more time than the 10‐ml (by 42 s, P = 0.002) or the 20‐ml (by 45 s, P = 0.001) syringes. The 60‐ml syringe also required significantly more time than the 10‐ml (by 64 s, P < 0.0001) or 20‐ml (by 67 s, P = 0.0001) syringe. Although all participants transferred the 250 ml, hand fatigue increased as syringe size increased: 5 ml (n = 3), 10 ml (n = 4), 20 ml (n = 7), and 60 ml (n = 15). Most participants preferred using the 10‐ml syringe (n = 11/20), followed by 20‐ml (n = 6/20), 5‐ml (n = 3/20), and 60‐ml (n = 0/20) syringes. Conclusion Manual fluid resuscitation using the 'pull and push' method is most rapidly accomplished with the 10‐ml or 20‐ml syringes. The 60‐ml syringe is associated with the most hand fatigue. Participants most preferred the 10‐ml or 20‐ml syringes.